Impact of dry eye on work productivity - Yamada, Masakazu (Dove Medical Press, 2012)
BACKGROUND: The purpose of this study was to evaluate the impact of dry eye on work productivity of office workers, especially in terms of presenteeism. METHODS: A total of 396 individuals aged ≥20 years (258 men and 138 women, mean age 43.4 ± 13.0 years) were recruited through an online survey. Data from 355 responders who did not have missing values were included in the analysis. They were classified into the following four groups according to the diagnostic status and subjective symptoms of dry eye: a definite dry eye group; a marginal dry eye group; a self-reported dry eye group; and a control group. The impact of dry eye on work productivity was evaluated using the Japanese version of the Work Limitations Questionnaire. The cost of work productivity loss associated with dry eye and the economic benefits of providing treatment for dry eye were also assessed. RESULTS: The degree of work performance loss was 5.65% in the definite dry eye group, 4.37% in the marginal dry eye group, 6.06% in the self-reported dry eye group, and 4.27% in the control group. Productivity in the self-reported dry eye group was significantly lower than that in the control group (P < 0.05). The annual cost of work productivity loss associated with dry eye was estimated to be USD 741 per person. CONCLUSION: Dry eye impairs work performance among office workers, which may lead to a substantial loss to industry. Management of symptoms of dry eye by providing treatment may contribute to improvement in work productivity.